The role of global traditional and complementary systems of medicine in the treatment of mental health disorders (2015)
Traditional and complementary systems of medicine include a broad range of practices, which are commonly embedded in cultural milieus and reflect community beliefs, experiences, religion, and spirituality. Two major components of this system are discernible: complementary alternative medicine and traditional medicine, with different clientele and correlates of patronage. Evidence from around the world suggests that a traditional or complementary system of medicine is commonly used by a large number of people with mental illness. Practitioners of traditional medicine in low-income and middle-income countries fill a major gap in mental health service delivery. Although some overlap exists in the diagnostic approaches of traditional and complementary systems of medicine and conventional biomedicine, some major differences exist, largely in the understanding of the nature and cause of mental disorders. Treatments used by providers of traditional and complementary systems of medicine, especially traditional and faith healers in low income and middle-income countries, might sometimes fail to meet widespread understandings of human rights and humane care. Nevertheless, collaborative engagement between traditional and complementary systems of medicine and conventional biomedicine might be possible in the care of people with mental illness. The best model to bring about that collaboration will need to be established by the needs of the extant mental health system in a country. Research is needed to provide an empirical basis for the feasibility of such collaboration, to clearly delineate its boundaries, and to test its effectiveness in bringing about improved patient outcomes.